The Influence of Cell Isolation and Culturing on Natriuretic Peptide Receptors in Aortic Vascular Smooth Muscle Cells - Rager, Christine; Klöpper, Tobias; Tasch, Sabine; Whittaker, Michael Raymond; Exintaris, Betty; Mietens, Andrea; Middendorff, Ralf; Justus Liebig University Giessen (My University, 2025)
Vascular smooth muscle cell (SMC) relaxation by guanylyl cyclases (GCs) and cGMP is mediated by NO and its receptor soluble GC (sGC) or natriuretic peptides (NPs) ANP/BNP and CNP with the receptors GC-A and GC-B, respectively. It is commonly accepted that cultured SMCs differ from those in intact vessels. Nevertheless, cell culture often remains the first step for signaling investigations and drug testing. Previously, we showed that even popular reference genes changed dramatically after SMC isolation from aorta. Regarding NP receptors, a substantial amount of data relies on cell culture. We hypothesize that the NP/cGMP system in intact aortic tunica media differs from isolated and cultured aortic SMCs. Therefore, we studied isolation and culturing effects on the expression of NP receptors GC-A, GC-B, and NP clearance receptor (NPRC) compared to sGC. We investigated intact tunica media and primary SMCs from the longitudinal halves of the same rat aorta. GC activity was monitored by cyclic guanosine monophosphate (cGMP). In addition, we hypothesize that there are sex-dependent differences in the NP/cGMP cascade in both intact tissue and cultured cells. We, therefore, analyzed a male and female cohort. Expression was quantified by RT-qPCR comparing aortic media and SMCs with our recently validated reference gene (RG) small nuclear ribonucleoprotein 2 (U2). Only GC-A was stably expressed. In intact media, GC-A exceeded GC-B and NPRC. However, GC-B, NPRC, and sGC were dramatically upregulated in cultured SMCs of the same aortae different from the stable GC-A. The expression was mirrored by NP-induced GC activity. In cultured cells, changes in GC activity were delayed compared to receptor expression. Minor differences between both sexes could also be revealed. Thus, isolation and culture fundamentally alter the cGMP system in vascular SMCs with potential impact on drug testing and scRNAseq. Especially, the dramatic increase in the clearance receptor NPRC in culture might distort all physiological ANP, BNP, and CNP effects.
Keywords: ddc:610